Determination of Effective Atomic Number of Rubber - Saion, Elias; Sulaiman, Zainal Abidin; Ahmad, Anuar; Wagiran, Husin (1983)
This paper reports a simple technique to determine the effective atomic number of rubber materials. The gamma ray attenuation coefficient of rubber was measured with high energy resolution Si(Li) detector at low gamma ray energies and the effective atomic number was determined by the functional ratio of attenuation coefficients at different energies. This study could provide a guide to an understanding of the quality of rubber based on its composition.